PENGARUH PENGGUNAAN MEDIA WORD SEARCH PUZZLE TERHADAP KETERAMPILAN MEMBACA SISWA DI SANGGAR BELAJAR KAMPUNG BHARU MALAYSIA - Annisa; Syamsuyurnita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using word search puzzle media on the skimming reading skills of fourth-grade students at Sanggar Belajar Kampung Bharu, Malaysia. The research employed a quasi-experimental method with a one group pretest–posttest design. The population consisted of 12 fourth-grade students. Data were collected through a skimming reading observation sheet that had been validated by a subject matter expert in Indonesian language education, and were analyzed using a paired sample t-test through SPSS 25.0. The results showed that the average score of students’ skimming reading skills was 52.50% in the pretest and 88% in the posttest. Based on the results of the hypothesis test, a significance value of 0.000 (<0.05) was obtained, indicating that the use of word search puzzle media has a significant effect on the skimming reading skills of fourth-grade students at Sanggar Belajar Kampung Bharu, Malaysia.